MIPO Technicque for Management of Distal Tibia Fractures Using LCPPrecontoured (3.5mm & 4.5mm) - A study Done in 250 Bedded General Hospital, Tangail (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Fractures of the distal tibia are unique in that the bone is subcutaneous with poor muscular coverage. Theconsequence of its decreased vascularity leads to complications like delayed bone union, wound complications suchas dehiscence and infection. These fractures can be managed with various techniques. Open reduction and internalfixation by plating, have been used with varying results. In current orthopedic practice, minimally invasivepercutaneous plating osteosynthesis (MIPO) and interlocking nailing are the preferred techniques for fractures of thedistal third tibia. In our study, twenty adult patients with closed fractures of distal tibia were treated with LCP usingMIPO technique & were followed for a period of one year (January 2014 to December 2014). Average age of patientsstudied was 40.5 years (18-55) with majority being high energy trauma (65% vs. 35%). Mean duration for surgeryfrom day of identification to go for surgery was 4-7 days. Results were evaluated clinically and radiologically. In 18cases (90%) fractures united & 2 cases (10%) had delayed union. All fractures were united by 20 weeks. Superficialskin infection was found in 2 cases, Valgus mal-alignment in 2 cases &1 case had ankle stiffness. Finally resultsshowed:10 cases (50%) had excellent outcome, 4 cases (20%) had good outcome, 4 cases (20%) had fair outcome,and 2 cases (10%) had poor outcome.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):09-13